Pesona Sriwijaya (Plant-based Recycling on Ecoprint Keramasan) Is an Urban Women Empowerment Program through the Production of Environmentally Friendly Traditional Cloth PT PLN Indonesia Power UPTD Keramasan - Maya Sari, Ira; Purwanto, Wahyu; Ghasani, Anindya; Bakhtiar Fahmi Fuadi (Prospect Publishing, 2023)
This article explains the conditions of the Palembang City women's empowerment program by optimizing the production of environmentally friendly traditional cloth. Namely, PT PLN Indonesia Power UPDK Keramasan assists in training in making environmentally friendly products, making environmentally friendly filters, and digital marketing. The women's empowerment program in Palembang City is implemented with a Triple Bottom Line approach which focuses on planet, people, and profit goals, so that the program implemented will have an impact not only on social and economic life but also on the environment so that the empowerment program will be sustainable. As a result, the beneficiary groups feel the positive impact, this program produces new groups that are active in empowerment, and there is an increase in members' income environmentally this program is also better because the fabric produced uses natural dyes and the processing uses a closed water system—this saving on water and electricity usage.